NUDT21 regulates lysyl oxidase-like 2(LOXL2) to influence ECM protein cross-linking in silica-induced pulmonary fibrosis - Lan Peng; Wenqing Sun; Demin Cheng; Xinying Jia; Wenxiu Lian; Ziwei Li; Haojie Xiong; Ting Wang; Yi Liu; Chunhui Ni (Ecotoxicology and Environmental Safety)
Silicosis is a disease caused by prolonged exposure to silica dust. It is the most typical, rapidly progressive, and fatal form of pneumoconiosis. Currently, there is no specific medication available for the treatment of silicosis. LOXL2 is a copper-dependent lysine oxidase whose main function is to catalyze the cross-linking of extracellular matrix components, particularly collagen and elastin. However, few researchers have investigated the role of LOXL2 in the pathogenesis of silicosis. In this study, we demonstrated that LOXL2 is upregulated in silica-inhaled mouse lung tissue and in a TGF-β-induced fibroblast model. In vitro, we confirmed that LOXL2 functions to promote ECM deposition by binding directly to collagen and elastin. We then used scavenger receptor cysteine-rich (SRCR) domains to show that LOXL2 can induce fibrosis independently of its enzymatic activity. Furthermore, we discovered that NUDT21, the LOXL2 upstream regulatory mechanism of LOXL2, alters LOXL2's 3′UTR usage by substituting alternative polyadenylation (APA), thereby modulating LOXL2 expression. By injecting LOXL2 siRNA-loaded liposomes into the tail vein of mice in the silica dust-treated mouse pulmonary fibrosis model, the severity of lung fibrosis was significantly reduced. In this context, LOXL2 is regulated by NUDT21 and may affect pulmonary fibrosis by influencing the cross-linking of ECM proteins. Our research provides a scientific basis for the development of new anti-fibrosis treatment strategies.